China Aggression in Indo Pacific: U.S. Strategies Toward Institutionalized Regional Security Bloc - Noraini Zulkifli (Asia Pacific Journal of Social Science Research, 2024)
China economic and military aggression in Indo Pacific has prompted the US to initiate strategic policy to strengthen its alliances in the region to a networked security architecture, capable of deterring aggression, maintaining stability, and ensuring free access to common domains, with possibility of Indo Pacific regional security alliance formation. For regional interest’s sake or preserving U.S. hegemony after humiliating withdrawal from the middle east, the research will ascertain real motives and proof the hypothesis with empirical evidence. This research highlights three objectives namely, to evaluate China aggression threat to Indo Pacific, study the institutionalized of Indo Pacific security alliance possibilities, and the impacts of alliance towards regional stability. It applies a qualitative method using empirical evidence from secondary data and performs content analysis from journal and document from official government and academic websites to proof the evidence validity before forming solid conclusion of the research findings. The research utilizes regional security complex and balance of power theory in ascertaining aggression validity and its’ relationship in influencing alliance formation that changes the geopolitics landscape, raising concern over its impact that will be analyzed to answer the research questions. Finding shows, the China threat is mere perception of the U.S concern about losing military hegemony and subsequently adversely impacting its economic might especially dollar as international currency while China coercion act is defensive act protecting its sovereignty. Justification for regional alliance is to preserve U.S. hegemony status quo at the expenses of regional member states. The U.S alliance would attract retaliation with China forming similar bloc that greatly impacted regional stability in four dimensions. The research concludes, China threats is self-defense act and manipulated by the U.S to justify its actions in forming regional alliance to remains a hegemonic at the cost of regional stability and members expenses.